Achievement of multiple therapeutic targets for cardiovascular disease prevention: Retrospective analysis of real practice in Italy. Issue 6 (5th June 2018) - Figliuzzi, Ilaria; Presta, Vivianne; Citoni, Barbara; Miceli, Francesca; Simonelli, Francesca; Battistoni, Allegra; Coluccia, Roberta; Ferrucci, Andrea; Volpe, Massimo; Tocci, Giuliano
Abstract : Background: Pharmacological therapy in patients at high cardiovascular (CV) risk should be tailored to achieve recommended therapeutic targets. Hypothesis: To evaluate individual global CV risk profile and to estimate the control rates of multiple therapeutic targets for in adult outpatients followed in real practice in Italy. Methods: Data extracted from a cross‐sectional, national medical database of adult outpatients in real practice in Italy were analyzed for global CV risk assessment and rates of control of major CV risk factors, including hypertension, dyslipidemia, diabetes, and obesity. CV risk characterization was based on the European SCORE equation and the study population stratified into 3 groups: low risk (<2%), intermediate risk (≥2%–<5%), and high to very high risk (≥5%). Results: We analyzed data from 7158 adult outpatients (mean age, 57.7 ±5.3 years; BMI, 28.3 ±5.0 kg/m 2, BP, 136.0 ±14.3/82.2 ±8.3 mm Hg; total cholesterol, 212.7 ±40.7 mg/dL), among whom 2029 (45.2%) had low, 1730 (24.2%) intermediate, and 731 (16.3%) high to very high risk. Increased SCORE risk was an independent predictor of poor achievement of diastolic BP <90 mm Hg (OR: 0.852, 95% CI: 0.822–0.882), LDL‐C < 130 mg/dL (OR: 0.892, 95% CI: 0.861–0.924), HDL‐C > 40 (males)/>50 (females) mg/dL (OR: 0.926, 95% CI: 0.895–0.958), triglycerides <160 mg/dL (OR: 0.925, 95% CI: 0.895–0.957), and BMI <25 kg/m 2 (OR: 0.888, 95% CI: 0.851–0.926), even after correction for diabetes, renal function, pharmacological therapy, and referring physicians ( P  < 0.001). Conclusions: Despite low prevalence and optimal medical therapy, individuals with high to very high SCORE risk did not achieve recommended therapeutic targets in a real‐world practice.